Measuring changes in financial and ecosystems service outcomes with simulated grassland restoration in a Corn Belt watershed - Audia, Ellen; Schulte, Lisa A.; Tyndall, John (Frontiers in Sustainable Food Systems, 2022)
While provisioning ecosystem services generated through agricultural production are high, this often comes at the expense of other ecosystem services. Approaches that support both farm income and a balanced array of ecosystem services are needed. We employed a landscape modeling approach to demonstrate the financial and ecosystem service outcomes of strategically restoring grassland cover within a Corn Belt agricultural watershed. We assessed potential changes associated with a “Baseline” land use scenario and two alternative scenarios for the Grand River Basin (Iowa and Missouri, USA). In a “Buffered” scenario we simulated the impacts of replacing cropland within 20 m of streams with restored native grassland cover. In a “Productivity-based” scenario we simulated the replacement of annual row crops on poorly performing croplands with native grassland cover. Grasslands comprised 0.4% of the Baseline scenario. Grassland was expanded to 0.8% of the watershed in the Buffered scenario, reducing annual nutrient and sediment loss by 1.44%, increasing soil carbon sequestration by 0.12% over 10 years, and increasing pollinator abundance by 0.01%. The estimated annual value of these enhancements was $1.7 million for nitrogen reduction, $0.1 million for phosphorus reduction, $0.5 million for sediment reduction, and $1.3 million for soil carbon sequestration. Grassland comprised 4.9% of the watershed in the Productivity-based scenario, reduced annual nutrient and sediment loss by 11.50%, increased soil carbon sequestration by 1.13% over 10 years, and increased pollinator abundance by 0.42%. The estimated annual value of enhancements was $18 million for nitrogen reduction, $1.4 million for phosphorus reduction, $2.5 million for sediment reduction, and $14 million for soil carbon sequestration. We also calculated the value of grassland biomass for a potential energy market. The benefit of producing and selling grassland biomass ranged -$445 to $1,291 ha/yr. Scaled to the watershed, annual revenues ranged -$7.3 million - $21.1 million for the Buffered scenario and -$44.2 million - $128.8 million for the Productivity-based scenario. This study was the first to quantify changes in revenue and the value of ecosystem services associated with grassland restoration in the Grand River Basin and can help inform discussion among watershed stakeholders.